Association of plasma branched‐chain amino acids with overweight: A Mendelian randomization analysis. Issue 10 (7th September 2021) - Liu, Lei; Wang, Xiaolin; Liu, Yang; Zhao, Xinjie; Xu, Zhiyong; Ma, Yanan; Xu, Guowang; Wen, Deliang
Abstract: Objective: A Mendelian randomization (MR) framework was applied to disentangle the causal effect of branched‐chain amino acids (BCAAs) and overweight/obesity in Chinese adolescents. Methods: Circulating BCAA levels were measured by liquid chromatography coupled with mass spectrometry. A total of 7 BCAAs and 12 BMI‐associated common variants identified from released genome‐wide association study results were genotyped. Furthermore, a bidirectional MR approach was undertaken to disentangle the causal effect of BCAAs and overweight/obesity, using two‐stage regression. Results: Using the inverse variance‐weighted strategy and the weighted genetic scoring instruments, the estimated odds ratio per 1‐arbitrary‐unit increase in the total BCAA level on overweight and obesity odds after adjusting for age and sex was 2.40 (95% CI: 1.38 to 3.42, p < 0.001) and 2.55 (95% CI: 1.35 to 4.82, p = 0.004), respectively. Furthermore, additional MR tests were undertaken using a reversed model, testing the causal effect of increasing BMI variants on total BCAA level. By contrast, no evidence that increased BMI was causally associated with the total BCAA level (estimated β associated with 1‐kg/m 2 increase in BMI = 0.05, 95% CI: −0.17 to 0.28, p = 0.642) was observed. Conclusions: In summary, BCAAs may be causally associated with overweight/obesity or, rather, a congenital dysmetabolism of BCAAs could be a cause of overweight/obesity in adolescents.